Functional Characterization of a Gene in Sedum alfredii Hance Resembling Rubber Elongation Factor Endowed with Functions Associated with Cadmium Tolerance - Liu, Mingying; Qiu, Wenming; He, Xuelian; Zheng, Liu; Song, Xixi; Han, Xiaojiao; Jiang, Jing; Qiao, Guirong; Sang, Jian; Liu, Mingqing; Zhuo, Renying (Frontiers in Plant Science, 2016)
Cadmium is a major toxic heavy-metal pollutant considering their bioaccumulation potential and persistence in the environment. The hyperaccumulating ecotype of Sedum alfredii Hance is a Zn/Cd co-hyperaccumulator inhabiting in a region of China with soils rich in Pb/Zn. Investigations into the underlying regulatory mechanisms of molecular Cd tolerance are of substantial interest. Library screening for genes related to cadmium tolerance resulted in the discovery of a gene resembling the rubber elongation factor gene and here it is designated as SaREFl based on the preliminary bioinformatics analysis. The heterologous expression of SaREFl rescued the growth of a transformed Cd-sensitive strain (ycf1). Furthermore, Cd tolerance was enhanced in Arabidopsis plants expressing SaREFl with improvement in the fresh weight and root length of seedlings, as well as physiological indexes of adult plants. The investigation of gene expression proﬁles exposed to four different heavy metal treatments found that SaREFl exhibited different modes of transcriptional regulation upon heavy metal excess responding most strongly to Cd and the root was the plant organ most sensitive to this heavy metal. Screening a S. alfredii Hance cDNA library using the yeast two-hybrid technology with SaREFl as a bait led to the identification of five target genes possibly interacting with SaREFl and a gene named prenylated Rab acceptor 1 (PRA1) domain protein which was detected with a high frequency. Subcellular localization revealed that SaREFl mainly distributed in the cytosol. Our findings would further enrich the connotation of REF-like genes and provide theoretical assistance for the application in breeding heavy metal-tolerant plants.